Media Transformation and Citizens’ Collective Consciousness in The Era of Digital Democracy - Mitra Mustaricha (Universitas Terbuka, 2025)
This study examines the transformation of media and its impact on the collective consciousness of citizens in the era of digital democracy in Indonesia. Democracy is not only realized through electoral procedures but also through processes of deliberation and state oversight. The transformation of media from traditional mass media to digital media has altered the ways in which citizens construct social realities and political solidarity. This article analyzes the role of media in shaping collective consciousness, from the homogenization of information during the New Order era to the fragmentation of information in the digital era. In this context, digital solidarity emerges through collective emotions rapidly disseminated via social media platforms, such as hashtags that instantly mobilize the masses. The article also addresses challenges posed by the power of social media and algorithms in shaping public opinion, which is often affective and episodic. Using a social constructionist theoretical framework, this article aims to understand how media transformation influences the quality of democracy and collective consciousness in Indonesian society